Search Result Enhancement For Arabic Datasets Using Modified Chicken Swarm - Abdul Hassan, Alia Karim; AbdulAmeer, Zainab (Iraqi Journal of Science, 2018)
The need for information web-searching is needed by many users nowadays. They use the search engines to input their query or question and wait for the answer or best search results. As results to user query the search engines many times may be return irrelevant pages or not related to information need. This paper presents a proposed model to provide the user with efficient and effective result through search engine, based on modified chicken swarm algorithm and cosine similarity to eliminate and delete irrelevant pages(outliers) from the ranked list results, and to improve the results of the user’s query . The proposed model is applied to Arabic dataset and use the ZAD corpus dataset for 27300 document. The experimental result shows that the proposed model improves the precision, recall, and accuracy. Thus the result produced by this method improves accuracy.